(Reading the markers in the internal public spaces in Iraq (international airports model - Al Bayati, Nemir Qassem Khalaf (Journal of Humanities & Social Sciences, 2017)
The problem of the study emphasized on recognizing the level of recognition of the addressee in reading the referential signs in the public interior spaces in Iraq through recognizing and comprehending the expressive theme. The study aimed at: recognizing the level of recognition of the addressee in reading the referential signs in the public interior spaces in Iraq. And recognizing the level of availability of such signs. The study comprised of: the subjective domain, represented in the internal general signs such as reading the symbols and the expressive meaning. The place domain is represented by the public interior spaces like international Iraqi airports. While in the time domain the study is the current situation of the community of the study in 2015. The study came up with some conclusions and recommendations. Such as the poor of the public interior spaces Important in Iraq for their users. And the inability to many users to recognize and comprehend the signs of the international internal references. Because of the weakness of the users for the weakness of the visual culture and the need of the public interior international spaces This led to the use of local referential signs coming from the local environment. The research came up with some recommendations that help the aim of the study.